(untitled) - Burroughs, William James (Cambridge,New York, 2003)
This completely updated edition explores in detail the unresolved debate on the existence of weather cycles. It provides a different perspective on one of the most difficult questions in the current global warming debate: how much of the recent temperature rise can be attributed to natural causes? The book examines the complex analysis required to assess the evidence for cycles with a minimum of mathematics
Keywords: Meteorology,Climatology,Khí tượng học; Periodicity